Cosmopolíticas, olhar e escuta: experiências cine-xamânicas entre os Maxakali - Ana Carolina Estrela da Costa (2015)
This work proposes, starting from ethnographic descriptions produced between Maxakali people, a brief analysis of his recent cinematrographic realization in a cosmopolitical context perceived and produced during the formation of filmmakers and production of films. I try to reconcile a reflection on Maxakali cosmopolitics actions, especially starting from the contributions of anthropologist Renato Sztutman, with understandings of cinema as an aesthetic and political experience, as the philosopher Jacques Rancière proposes, and as the possibility of shared ethnographic creation, as suggested by ethnologist-filmmaker Jean Rouch. The objective is to present an ethnography of filmmakers formation and in which these films are made: the moments of negotiation, drafting, production of images and the meetings that these images cause, in which such technology is appropriated by them in resonance with their own ways of thinking and organization. We will see how the shamans and chiefs seem to have found a place that seems to suggest a close approximation between languages and actions under the policy, shamanism and cinema. After all, the movie seems appropriate for the event-encounters experience that take place in the villages, and the establishment of new alliances and exchanges of knowledge out of them.